Comparison of Droplet Digital PCR to Real-Time PCR for Quantitative Detection of Cytomegalovirus - Hayden, R. T. (American Society for Microbiology, 2013)
Quantitative real-time PCR (QRT-PCR) has been widely implemented for clinical viral load testing, but a lack of standardization and relatively poor precision have hindered its usefulness. Digital PCR offers highly precise, direct quantification without requiring a calibration curve. Performance characteristics of real-time PCR were compared to those of droplet digital PCR (ddPCR) for cytomegalovirus (CMV) load testing. Tenfold serial dilutions of the World Health Organization (WHO) and the National Institute of Standards and Technology (NIST) CMV quantitative standards were tested, together with the AcroMetrix CMV tc panel (Life Technologies, Carlsbad, CA) and 50 human plasma specimens. Each method was evaluated using all three standards for quantitative linearity, lower limit of detection (LOD), and accuracy. Quantitative correlation, mean viral load, and variability were compared. Real-time PCR showed somewhat higher sensitivity than ddPCR (LODs, 3 log(10) versus 4 log(10) copies/ml and IU/ml for NIST and WHO standards, respectively). Both methods showed a high degree of linearity and quantitative correlation for standards (R(2) ≥ 0.98 in each of 6 regression models) and clinical samples (R(2) = 0.93) across their detectable ranges. For higher concentrations, ddPCR showed less variability than QRT-PCR for the WHO standards and AcroMetrix standards (P < 0.05). QRT-PCR showed less variability and greater sensitivity than did ddPCR in clinical samples. Both digital and real-time PCR provide accurate CMV load data over a wide linear dynamic range. Digital PCR may provide an opportunity to reduce the quantitative variability currently seen using real-time PCR, but methods need to be further optimized to match the sensitivity of real-time PCR.